Micro-Agrivoltaics: Hiding in plain sight - Verma, Shilp; Usadadia, Nikunj; Kuriachen, Philip; Anand, Abhishek (International Institute for Sustainable Development, 2025)
As India explores the promise of agrivoltaics, small and marginal farmers are cultivating crops beneath solar panels without formal support or mainstream recognition. Researchers at the International Water Management Institute-Tata Water Policy Program (ITP) argue that this under-recognized practice of ‘Micro-Agrivoltaics” is a powerful opportunity to scale clean energy while boosting agricultural productivity and deserves greater attention and systematic study.